Reuse of medical face masks in domestic and community settings without sacrificing safety: Ecological and economical lessons from the Covid-19 pandemic. (February 2022) - Alcaraz, Jean-Pierre; Le Coq, Laurence; Pourchez, Jérémie; Thomas, Dominique; Chazelet, Sandrine; Boudry, Isabelle; Barbado, Maud; Silvent, Sophie; Dessale, Claire; Antoine, Fabienne; Guimier-Pingault, Catherine; Cortella, Laurent; et al.
Abstract: The need for personal protective equipment increased exponentially in response to the Covid-19 pandemic. To cope with the mask shortage during springtime 2020, a French consortium was created to find ways to reuse medical and respiratory masks in healthcare departments. The consortium addressed the complex context of the balance between cleaning medical masks in a way that maintains their safety and functionality for reuse, with the environmental advantage to manage medical disposable waste despite the current mask designation as single-use by the regulatory frameworks. We report a Workflow that provides a quantitative basis to determine the safety and efficacy of a medical mask that is decontaminated for reuse. The type IIR polypropylene medical masks can be washed up to 10 times, washed 5 times and autoclaved 5 times, or washed then sterilized with radiations or ethylene oxide, without any degradation of their filtration or breathability properties. There is loss of the anti-projection properties. The Workflow rendered the medical masks to comply to the AFNOR S76-001 standard as "type 1 non-sanitory usage masks". This qualification gives a legal status to the Workflow-treated masks and allows recommendation for the reuse of washed medical masks by the general population, with the significant public health advantage of providing better protection than cloth-tissue masks. Additionally, such a legal status provides a basis to perform a clinical trial to test the masks in real conditions, with full compliance with EN 14683 norm, for collective reuse. The rational reuse of medical mask and their end-of-life management is critical, particularly in pandemic periods when decisive turns can be taken. The reuse of masks in the general population, in industries, or in hospitals (but not for surgery) has significant advantages for the management of waste without degrading the safety of individuals wearing reused masks. Highlights: 10 cycles of washing or 5 washing followed by 5 autoclaving cycles have been tested. Medical masks can be reused up to 10 times with a cleaning method between each use. Masks retain their breathability/filtration capability after 10 cycles of cleaning. Treated masks lack of their CE marking but are qualified with S76-001 AFNOR norm. Pragmatic guidance will allow to generate 10 times less plastic in the environment.